Sistem Pendukung Keputusan Pemilihan Lokasi Site untuk Pemasangan Sistem Telekomunikasi Baru dengan Metode Fuzzy Multi-Criteria Decision Making (Lembaga Pengembangan Kinerja Dosen, 2021)
The project facilities and infrastructure are well-known for their large investment, high risk and long repair time. For companies engaged in technical services and telecommunication system planning, the focus of investment in project facilities and infrastructure is the effectiveness and choice of system placement location. Therefore, it is important for these companies to plan and decide on the placement of appropriate and good facilities and infrastructure so that the system can be used effectively and optimally for telecommunications companies. Making decisions regarding the placement of the right system is indeed not easy because of the uncertainty that is always inherent in the location selection process, especially those that are too complex and the variety of data or information available and the difficulty of knowing the certainty of the data and information. which was developed using the fuzzy Promethee method can be used to optimize the decision-making process so that the factors that influence decision-making are definite and clear to be used in calculations.